The book of all books - Calasso, Roberto; Parks, Tim (New York : Farrar, Straus and Giroux, 2021)
"A book that begins before Adam and ends after us. In this magisterial work, figures of the Bible and its whole outline emerge in a new light: one that is often astonishing and disquieting, as indeed is the book from which they originate"--
"Originally published in Italian in 2019 by Adelphi Edizioni, Italy, as Il libro di tutti i libri."
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc